Russian Fertility Database - Elena V. Churilova; Evgeny M. Andreev; Kirill O. Chertenkov; Pavel A. Kishenin; Olga A. Rodina; Vera V. Sokolova (Население и экономика)
The Russian Fertility Database contains a series of fertility indicators by birth order for Russia from 1946 to 2022, cohort fertility tables by birth order, and fertility rates by birth order for Russian women born between 1932 and 1988. All fertility indicators are calculated using data from official population statistics provided by the Federal State Statistics Service. The article describes the structure of the database, the source data, and the methodology of calculating period and cohort fertility rates, as well as cohort fertility tables by birth order. The Russian Fertility Database can be used for research, analytical materials, reports, presentations, as well as for educational purposes. The data allow us to analyze changes in the age profiles of fertility, the mean age at birth, the dynamics of the total fertility rate as period and cohort indicator for all birth orders combined and by birth order, parity distribution of women with specific number of children ever born and parity progression ratios. The data are in .xlsx format and are available on the web page: https://demogr.hse.ru/RFD.